Epidemic trend of Salmonella from swines and broilers in China from 2014 to 2023 and genetic evolution analysis of ESBLs-producing strains - Liu, Yaopeng; Wang, Lin; Wang, Juan; Lu, Mingzhe; Liu, Na; Zhao, Jianmei; Hu, Fangyuan; Han, Keguang; Liu, Junhui; Wang, Junwei; Qu, Zhina (Frontiers in Microbiology, 2025)
IntroductionIn recent years, the epidemic trend and antimicrobial resistance of Salmonella from swines and broilers, especially the extended-spectrum β-lactamase (ESBLs)-producing Salmonella, pose a serious threat to human and animal health.MethodsIn this study, we employed serotype identification, drug sensitivity testing, detection of ESBL-producing strains, and whole genome sequencing to analyze the epidemiological trends and drug resistance of Salmonella isolates from swines and broilers, as well as the genetic evolutionary relationships of ESBL-producing strains in China from 2014 to 2023.ResultsThe results showed that the most prevalent serotypes of Salmonella from swines and broilers in China in recent 10 years were S. Typhimurium (133/381, 34.91%) and S. Enteritidis (156/416, 37.50%), respectively. Overall, 80.58% strains from swines and 70.67% strains from broilers were multidrug resistant. The multidrug resistance rate (MDR) showed a downward trend. The types of drugs exhibiting an increasing trend in resistance rates among Salmonella from broilers (7) were significantly greater than those from swines (2). The detection rates of ESBLs-producing Salmonella from swines and broilers were 9.45 and 29.58%, respectively, with the former showing a downward trend and the latter showing an upward trend. The drug resistance phenotype of Salmonella produced in ESBLs from swines and broilers is consistent with the results of the resistance genes carried. Whole genome sequencing analysis revealed that 36 swine-derived ESBL-producing Salmonella strains contained 6 ST-types and 13 cgST-types, among which ST34 and ST17 were dominant ST-types; a total of 35 resistance genes across 11 classes, blaCTX-M-14, blaTEM-1B, and blaCTX-M-65 were the predominant subtypes of β-lactam resistance genes. 126 broiler-derived ESBL-producing Salmonella strains included 19 ST-types and 37 cgST-types, with ST17 and ST198 as the dominant ST-types; a total of 52 resistance genes belonging to 12 classes, blaCTX-M-55, blaCTX-M-65, blaTEM-1B, and blaOXA-1 identified as the major subtypes of β-lactam resistance genes.DiscussionThis suggests that we should thoroughly implement management policies aimed at reducing the use of veterinary antimicrobials. Additionally, we should enhance research on traceability technology and the abatement of resistance genes, thereby providing support for the effective prevention and control of the spread of Salmonella and its drug resistance.